Knowledge and attitude towards identification and management of sepsis among resident physicians in tertiary care teaching hospital in Pakistan - Ainan Arshad; Abdul Aziz; Ahmed Ayaz; Syed Maaz Salahuddin; Bushra Jamil (Journal of the Pakistan Medical Association, 2021)
We conducted this study to determine the compliance and knowledge of sepsis guidelines among resident physicians in tertiary care hospital of developing country. A self-structured validated questionnaire was prepared to evaluate compliance and knowledge of the SSC guidelines. A total of 76 resident physicians completed the questionnaire; 51 (67%) were Internal Medicine Residents and 25 (33%) were Emergency Medicine residents of Aga Khan University Hospital. 93% of the participants claimed to be aware of the SSC guidelines but only 26% considered themselves very knowledgeable on the subject. Less than half of them confessed to using the guidelines regularly. We concluded that the overall knowledge and compliance of sepsis guidelines was suboptimal. This highlights the need for increased awareness and teaching of sepsis and SSC guidelines to improve patient outcomes in developing countries. Keywords: Sepsis knowledge; health education, Continuous...